A Hybrid Nine-level Inverter Topology for an Open-end Stator Winding Induction Motor. Issue 16 (1st October 2016) - Kumar, Sanjiv; Agarwal, Pramod
Abstract: In this article, a new hybrid nine-level inverter topology for an induction motor with an open-end stator winding is proposed. In the proposed topology, one end of the open-end winding is fed by a three-phase five-level inverter, and the other end is connected to a conventional three-phase two-level inverter. The three-phase five-level structure is realized by cascading a three-level flying capacitor inverter with capacitor-fed H-bridge in each phase. In the proposed topology, a total of 17, 576 space vector combinations are available; hence, the capacitor voltages can be maintained at desired levels using switching redundancies. As compared to conventional topologies that require 48 switches, the proposed topology requires only 30 switches and completely eliminates the requirement of clamping diodes, which are required in a neutral point clamped inverter. Also, it requires only two capacitors per phase, whereas the nine-level flying capacitor inverter requires 28 capacitors per phase. In case of fault in any H-bridge, the system can be operated as a five-level inverter at its full power rating and improves the reliability of the inverter. The performance of the proposed system has been experimentally investigated on a 1.5-kW open-end stator winding induction motor, and results are presented.